Effect of several tuba leaves (Derris elliptica (Wallich) Benth.) Extract concentrations on mortality of rice brown planthopper (Nilaparvata lugens Stal) - Rusli Rustam; Rizke Skar Nolla Utari; Mukhlis Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Brown Planthoppers (BPH) (Nilaparvata lugens Stal) are the main pests of rice. It causes plant damage by sucking the sap from the stem, inhibiting growth, and causing plant failure. Infestation by N. lugens can reduce yields by up to 100%. The use of plant-based insecticides is one of the efforts to control insect pest infestations. Tuba plant (Derris elliptica (Wallich) Benth.) is one of the potential plants that can be used as botanical insecticides. The purpose of this research was to determine the effective concentration of tuba leaf extract against the mortality of N. lugens. This research was conducted at the Plant Pest Laboratory, Faculty of Agriculture, Universiti Riau, Indonesia from January to March 2023 using a Completely Randomized Design (CRD) with five treatments and four replications. The concentrations of tuba leaf extract with water as a solvent consisted of concentrations P0: 0%, P1: 2.5%, P2: 5%, P3: 7.5%, and P4: 10%. The results showed that the application of tuba leaf extract had a significant effect on the mortality of N. lugens. The concentration of 7.5% tuba leaf extract was effective in controlling BPHs as it was able to cause a mortality rate of 82.50% with an initial mortality time of 4.50 hours after application and a time to 50% mortality of 20.75 hours after application. In addition, the concentrations of tuba leaf extract for LC50 and LC95 lethality of N. lugens were 1.46% (14.6 g/L) and 23.29% (232.9 g/L), respectively.